2011
DOI: 10.1017/jfm.2011.19
|View full text |Cite
|
Sign up to set email alerts
|

Spatial resolution correction for wall-bounded turbulence measurements

Abstract: A correction for streamwise Reynolds stress data acquired with insufficient spatial resolution is proposed for wall-bounded flows. The method is based on the attached eddy hypothesis to account for spatial filtering effects at all wall-normal positions. This analysis reveals that outside the near-wall region the spatial filtering effect scales inversely with the distance from the wall, in contrast to the commonly assumed scaling with the viscous length scale. The new formulation is shown to work very well for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(61 citation statements)
references
References 31 publications
5
56
0
Order By: Relevance
“…The pipe data are plotted for y + > 10 at the lowest three Re τ (Re τ 5400) but only for y + > 300 at higher Re τ in order to stay clear of spatial resolution issues (cf. Smits et al 2011). In general, very good agreement is observed between the two geometries even at 10th order with possibly a slight trend of increasing E * p,1 with increasing Re τ in the pipe.…”
Section: Universality Of the Ratiosmentioning
confidence: 59%
“…The pipe data are plotted for y + > 10 at the lowest three Re τ (Re τ 5400) but only for y + > 300 at higher Re τ in order to stay clear of spatial resolution issues (cf. Smits et al 2011). In general, very good agreement is observed between the two geometries even at 10th order with possibly a slight trend of increasing E * p,1 with increasing Re τ in the pipe.…”
Section: Universality Of the Ratiosmentioning
confidence: 59%
“…In real flows, modes associated with the near-wall cycle (λ + x ≈ 10 3 , c + ≈ 10-12) are known to be the most energetic at low Reynolds number (Monty et al 2009;Smits et al 2011). So, the energy content predicted by a broadband forcing assumption does not exactly match the energy content in real flows.…”
Section: Effect Of Opposition Control In Spectral Spacementioning
confidence: 98%
“…Of course, these results must be interpreted with some caution since the broadband forcing assumption employed here does not accurately capture the uncontrolled energy spectrum in the real flow. However, it is generally true that longer faster-moving modes become more energetic at higher Reynolds number (Smits et al 2011). …”
Section: Effect Of Opposition Control In Spectral Spacementioning
confidence: 99%
“…Although the streamwise variance profile exhibits a mild second peak, the fact that the wire length in inner units L + increases up to 40 and 80 viscous units for the boundary-layer and Dantec probes, respectively, excludes the possibility of drawing any firm conclusions regarding this. By utilizing the spatial resolution correction outlined in [28], it was found that the entire range covered by the X-wire measurements is virtually free of spatial resolution effects. The near-wall data from the single wires, on the other hand, are affected and the results from the correction scheme are shown in figure 5a as grey symbols.…”
Section: Reynolds Stresses (A) Streamwise Componentmentioning
confidence: 99%